Standardization of the "Perceptual modeling" Test for Children 5-6 and 6-7 Years old - D.V. Chumachenko; E.K. Yaglovskya (Психолого-педагогические исследования, 2024)
In modern sociocultural conditions, reliable diagnostic tools are needed to assess the mental development of a child, which would at the same time make it possible to adjust the objectives of educational work. The article reflects the results of adaptation and standardization of the "Perceptual modeling" test included in the diagnostic set for assessing the mental development of preschoolers (L.A. Wenger and colleagues). The study sample consisted of two groups: children 5-6 (N=1003) and children 6-7 (N=1516) years old. In these groups, children were offered various test options based on their age-related perceptual modeling capabilities. The adaptation of the "Perceptual modeling" test involved converting it into electronic form, changing the system for evaluating the results obtained and statistically verifying the possibility of using it in this form to solve diagnostic problems. The test standardization procedure has shown good external and internal validity, and its diagnostic reliability. Statistical analysis revealed the absence of significant gender differences in the performance of the test and the presence of significant differences between children with normal development and children with disabilities (speech, hearing impairment and mental retardation). As a result of standardization, age norms for mastering perceptual modeling actions for children with normal development and children with disabilities were determined by children of the sixth and seventh years of life.